Relationship between Pre-Section Anxiety and Postpartum Quality of Life - Srimiyati, Srimiyati; Ajul, Keristina; Pascalina, Victorina; Br. Pakpahan, Dahlia Dominica (Electronic Journal of Education, Social Economics and Technology, 2025)
Anxiety before undergoing Sectio Cesarea (SC) has the opportunity to disrupt the quality of life during the postpartum period, both physically, psychologically, and socially. This study analyzed the relationship between anxiety before SC and the quality of life of postpartum women. SC delivery is the choice of women for maternal and infant health reasons and for the choice of birth date. The act of SC is inseparable from the act of severing tissue. Even though SC is the choice of the woman who will give birth, this action causes fear and anxiety in her. In addition, the wound in the incision is the cause of pain after SC. Surgical wound pain is often a trigger for discomfort and limitation of movement. The quality of life of postpartum women is part of their satisfaction with their condition. Postpartum women who have not been able to adapt to their condition can interfere with their well-being.